Treatment of hypothalamic obesity in people with hypothalamic injury: new drugs are on the horizon - Roth, Christian L.; Zenno, Anna (Frontiers in Endocrinology, 2023)
Hypothalamic obesity (HO) is a complex and rare disorder affecting multiple regulatory pathways of energy intake and expenditure in the brain as well as the regulation of the autonomic nervous system and peripheral hormonal signaling. It can be related to monogenic obesity syndromes which often affect the central leptin-melanocortin pathways or due to injury of the hypothalamus from pituitary and hypothalamic tumors, such as craniopharyngioma, surgery, trauma, or radiation to the hypothalamus. Traditional treatments of obesity, such as lifestyle intervention and specific diets, are still a therapeutic cornerstone, but often fail to result in meaningful and sustained reduction of body mass index. This review will give an update on pharmacotherapies of HO related to hypothalamic injury. Recent obesity drug developments are promising for successful obesity intervention outcomes.